Rice Expression Database (RED): An integrated RNA-Seq-derived gene expression database for rice. (20th May 2017) - Xia, Lin; Zou, Dong; Sang, Jian; Xu, Xingjian; Yin, Hongyan; Li, Mengwei; Wu, Shuangyang; Hu, Songnian; Hao, Lili; Zhang, Zhang
Abstract: Rice is one of the most important stable food as well as a monocotyledonous model organism for the plant research community. Here, we present RED (Rice Expression Database;http://expression.ic4r.org ), an integrated database of rice gene expression profiles derived entirely from RNA-Seq data. RED features a comprehensive collection of 284 high-quality RNA-Seq experiments, integrates a large number of gene expression profiles and covers a wide range of rice growth stages as well as various treatments. Based on massive expression profiles, RED provides a list of housekeeping and tissue-specific genes and dynamically constructs co-expression networks for gene(s) of interest. Besides, it provides user-friendly web interfaces for querying, browsing and visualizing expression profiles of concerned genes. Together, as a core resource in BIG Data Center, RED bears great utility for characterizing the function of rice genes and better understanding important biological processes and mechanisms underlying complex agronomic traits in rice.